An empirical analysis of the impact of textile professional market on the regional economy. (2015) - Hang, Ye; Hongjian, Qu; Sun, Yu
Textile industry is a traditional pillar industry in China, in the process of industrialisation, it has accumulated a large number of funds for the construction of national economy. At the same time, along with the development of many professional textile and garment markets, they have made great contributions in promoting the development of the regional economy. In order to study the impact of textile professional market on the regional economy, this paper use oriental silk professional market and Suzhou (2001-2011) regional economy data; Textile City professional market and Shaoxing (2001-2011) regional economy data as samples and have an empirical analysis of the impact of the textile professional market on the regional economy. This paper will extract common factors of regional economy indicators as explained variables through factor analysis. The study found the following conclusions: oriental silk professional market, the size of the textile professional market, improvement of directors' average compensation and the good modest growth of shareholders' equity can promote the development of regional economy. And such as earnings per share, gross profit, sales revenue of the top five customers, operating room rental gross margin have no obvious effects on the regional economy development. The development of Textile City professional markets in our analysis is more mature than the Oriental silk professional market.